Identification of strategies to reduce accidents and losses in drilling industry by comprehensive HSE risk assessment—A case study in Iranian drilling industry. (November 2016) - Amir-Heidari, Payam; Maknoon, Reza; Taheri, Bahram; Bazyari, Mahdieh
Abstract: Drilling industry, because of the particular conditions relating to its nature, is one of the high-risk and hazardous sectors of petroleum industry. Major and minor accidents in this industry cause losses of lives and result in financial and reputational losses. The first step to reduce accidents and losses in this industry is identification and assessment of the attended risks. After this, the risks can be prioritized in terms of their importance, and then proper long-term strategies to reduce the accidents can be identified and implemented. In this article, with a study of past research and accident statistics and reports, and using standards checklists and expert opinion, significant HSE risks in Iranian drilling industry were identified and assessed with a new structured method. The result of scrutiny of the 60 identified risks showed that management, human and hardware are, respectively, the most important influential factors in accident causation. The results of the assessment of the 20 most important risks also showed that the level of the most of these risks, despite existing controls, was still in unacceptable area. It is expected that with implementation of the controls proposed in this research, the risks will be reduced to an acceptable level. The priority of the strategies to reduce incidents in Iranian drilling industry should be development of long-term strategic plans for implementation of the proposed controls. The method used in this research and the results can be used to reduce accidents in drilling industry worldwide. Highlights: Comprehensive risk identification in Iranian drilling industry was performed by the study of past research, checklist and expert opinion. The risk assessment and control analysis were done using a new methodology. Seven categories of consequences were used in risk assessment. Three levels of risk were assessed (pure risk, residual risk 1 and residual risk 2). Management, human and hardware are the most important factors affecting the accidents in drilling industry.